Transformation of the Values of the Sīrah Nabawiyyah in Generation Z - Abdiguno, Panggih; Luhuringbudi, Teguh; Kuliyatun; Masuwd, Mowafg Abrahem; Utami, Dewi Nita (Jurnal Pendidikan Islam, 2025)
This study emphasizes the transformation of the values ​​of the Sīrah Nabawiyyah in the context of character education for Generation Z, while identifying the challenges and opportunities in integrating these values ​​into modern education. The key objective of this study is to analyze and understand how the younger generation can relate lessons from the Sīrah to the context of their daily lives. Data have been collected through questionnaires distributed to 203 students, as well as narrative analysis of relevant literature to understand the values ​​in the Sīrah. The application of analytical methods has included the Theory of Character Education by Lickona and the Theory of Contextual Learning by Dewey, with primary sources in the form of Sīrah books and character education documents. The findings have shown that students tend to prioritize understanding the historical context and the suitability and harmony of Islamic values ​​in modern life, so suggestions for further research are to explore the combination of religious education and active learning. Despite the limitations in the number of respondents, this study provides a significant contribution to the development of appropriate, responsible, and applicable Islamic values-based learning methods, and paves the way for further exploration of the long-term impacts of character education in diverse contexts.